PENGUATAN LITERASI DIGITAL GENERASI Z DALAM PEMBELAJARAN PAI DI TENGAH ARUS INFORMASI KEAGAMAAN DIGITAL - Abdul Halim Rais (Berajah Journal, 2026)
The ever-increasing flow of digital religious information has placed Generation Z in a complex situation, as access to religious knowledge has become more open, yet at the same time they are vulnerable to hoaxes, misinformation, disinformation, hate speech and an incomplete understanding of religion. This study aims to examine the strengthening of Generation Z’s digital literacy in Islamic Religious Education amidst the development of digital religious information. This study employs a descriptive qualitative approach in the form of a literature review. Data were obtained from journal articles, books, policy documents and relevant research findings, and were subsequently analysed using content analysis techniques. The findings indicate that digital literacy in Islamic Religious Education encompasses technical skills, critical thinking, media ethics and spiritual awareness. These four aspects need to be integrated with the principle of tabayyun so that learners are able to assess, verify and disseminate religious information wisely. This study contributes by offering a framework for strengthening religious digital literacy that is relevant to Islamic Religious Education and the development of Generation Z’s digital character.